A novel validated assay to support the discovery of new anti-malarial gametocytocidal agents. (December 2016) - Bahamontes-Rosa, Noemí; Gomez-Lorenzo, María; Lelièvre, Joël; Rodriguez Alejandre, Ane; Almela, María; Lozano, Sonia; Herreros, Esperanza; Gamo, Francisco-Javier
Abstract Background Drugs that kill or inhibitPlasmodium gametocytes in the human host could potentially synergize the impact of other chemotherapeutic interventions by blocking transmission. To develop such agents, reliable methods are needed to study the in vitro activity of compounds against gametocytes. This study describes a novel assay for characterizing the activity of anti-malarial drugs against the later stages ofPlasmodium falciparum gametocyte development using real-time PCR (qPCR). Methods Genes previously reported to be transcribed at the different sexual stages of the gametocytogenesis were selected for study and their mRNA expression was measured in a gametocytogenesis course by qPCR. Genes mainly expressed in the later stages of gametocyte development were used as a surrogate measurement of drug activity. To distinguish between cidal and static drug effects, two different experiments were performed in parallel, one with constant drug pressure throughout the experiment (144 h), and another in which the gametocyte cultures were exposed to the compound for only 48 h. Results FourP. falciparum genes coding for proteins Pf77, ROM3, Pfs25, and Pfg377 with transcription specific for late-stage gametocyte development were identified. The in vitro anti-malarial activity of compounds against such gametocytes was assessed by measuring mRNA levels of these genes using qPCR. The assay was validated against standard anti-malarial drugs (epoxomicin, dihydroartemisinin, chloroquine, thiostrepton, and methylene blue) and compounds from the GSK compound library with known anti-gametocyte activity. Conclusions This study describes a novel assay for characterizing the activity of anti-malarial drugs against the later stages ofP. falciparum gametocyte development using qPCR in genetically unmodified parasites. The method described is a reliable and user-friendly technique with a medium throughput that could be easily implemented in any laboratory.